2010
DOI: 10.1007/s11151-010-9257-5
|View full text |Cite
|
Sign up to set email alerts
|

eBay in the Economic Literature: Analysis of an Auction Marketplace

Abstract: This survey brings together theoretical and empirical questions that have been addressed in the economic literature on eBay, focusing on understanding the behavior of buyers and sellers. We discuss several puzzles of bidder behavior and the explanations that have been put forward by the literature for each. We then discuss structural estimates of bidder behavior and measuring the consumer surplus derived from eBay. We then try to understand why there are so many selling formats being used simultaneously, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 89 publications
(145 reference statements)
1
37
0
1
Order By: Relevance
“…There was, however, a significant difference between the sellers' reputation. The sellers in the 11 Pure auctions and fixed-price auctions must end with the formats they start with, but BIN auctions can end with a bidder winning either with competitive bid or BIN. This is because once a bidder places a bid, BIN disappears and the auction becomes a pure auction.…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was, however, a significant difference between the sellers' reputation. The sellers in the 11 Pure auctions and fixed-price auctions must end with the formats they start with, but BIN auctions can end with a bidder winning either with competitive bid or BIN. This is because once a bidder places a bid, BIN disappears and the auction becomes a pure auction.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Since eBay facilitates a fixed-price purchase with BIN in which the buyers are not allowed to place bids, what we call the "fixed-price" auction in this paper is called a BIN auction in some other papers (e.g., Hasker and Sickles, 2010). Also, although fixed-price format is not an auction per se, we call it a fixed-price "auction" for the sake of convenience in explanation.…”
mentioning
confidence: 99%
“…no price price dispersion). Hasker and Sickles (2010) use the incremental bidding prediction of the bidding rule in PS as a simple explanation for sniping in eBay. Zeithammer and Adams (2010) use data on eBay auctions to reject the hypothesis that these auctions resemble second-price sealed-bid auctions and use PS bidding rule as potential model consistent with some of their findings.…”
Section: Introductionmentioning
confidence: 99%
“…Some reviews of the empirical literature applied to this environment can be found in Ockenfels et al (2006) and Hasker and Sickles (2010). A more general review of previous literature regarding field experiments and empirical work on auctions is presented by LuckingReiley et al (2007).…”
Section: Introductionmentioning
confidence: 99%